Application of Park's power components to the differential protection of three-phase transformers - Oliveira, L. M. R. (2014)
This paper presents a new scheme for power transformers differential protection, in which the concept of the Park's instantaneous differential powers is introduced. The proposed method is able to detect winding insulation failures and to distinguish them from magnetizing inrush current transients. Experimental and simulation results are presented and discussed.